2022
DOI: 10.1007/s00167-022-06979-4
|View full text |Cite
|
Sign up to set email alerts
|

Individualized tibial tubercle–trochlear groove distance-to-patellar length ratio (TT–TG/PL) is a more reliable measurement than TT–TG alone for evaluating patellar instability

Abstract: Purpose To evaluate the intra/inter-rater and diagnostic reliability of the sagittal plane adjusted patellar instability ratios (PIRs) compared to tibial tubercle-trochlear groove (TT-TG) distance alone while employing a matched case-control analysis for age and sex to minimize a potential confounding efect. Methods A retrospective case-control study was performed of all knee MRI studies of patients diagnosed with patellar instability, between 2005 and 2020 at a regional tertiary medical centre. Using a 1:1 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, both the MPFLR and MPFLR+TTT groups showed acceptable CMS values. It is noteworthy that TT‐TG distance is a crucial factor in knees with patellar instability 23 . Moreover, a previous study has suggested a prognostic impact of TT‐TG distance following MPFLR 15 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, both the MPFLR and MPFLR+TTT groups showed acceptable CMS values. It is noteworthy that TT‐TG distance is a crucial factor in knees with patellar instability 23 . Moreover, a previous study has suggested a prognostic impact of TT‐TG distance following MPFLR 15 .…”
Section: Discussionmentioning
confidence: 94%
“…It is noteworthy that TT-TG distance is a crucial factor in knees with patellar instability. 23 Moreover, a previous study has suggested a prognostic impact of TT-TG distance following MPFLR. 15 However, the four studies that were selected in our study had inconsistent TT-TG values, which may introduce bias to the results.…”
Section: Limitationmentioning
confidence: 99%